Dyslipidaemia and glaucoma - Jünemann, Anselm; Huchzermeyer, Cord; Rejdak, R.; Hohberger, B. (Klinische Monatsblätter für Augenheilkunde, 2014)
Endothelial dysfunction and vascular dysregulation play a role in the multifactorial pathogenesis of glaucomatous optic nerve atrophy. Dyslipidaemia as a risk factor for endothelial dysfunction is associated with glaucoma and cardiovascular morbidity and mortality. In additional to a genetic disposition, a potential mechanism for the pathogenesis of endothelial dysfunction could be an additive effect of several risk factors, like dyslipidaemia, smoking, arterial hypertension, diabetes and hyperhomocysteinaemia. This paper reviews the literature concerning the association between dyslipidaemia and glaucomatous disease and explains the possible role of dyslipidaemia for the pathogenesis and progression of glaucoma. The role of exogeneous modifiable risk factors for prevention and therapy of glaucoma and their neutralisation by changing life style like weight reduction, modifications of nutrition and physical activity, are discussed.
EVALuna2:21178